A study of arbitration method for determination of shale brittleness index - Jian Min; Jian Yang; Fei Liu; Ze Li; Yuntao Liu; Jun Su; Wende Yan (AIP Advances)
The ambiguous definitions of both brittleness and compressibility have led to longstanding debate on the characterization of shale brittleness. To resolve this, this study proposes a standardized shale brittleness index (SBI), defined as propensity of shale to breaking with minimal plastic deformation under tensile, shear, and compressive loads under standard conditions (20 °C, 101.325 kPa), clarifying its distinction from compressibility. Building upon material brittleness concepts and fracture mechanics, an arbitration method for SBI determination was developed by integrating three normalized components—peak stress-to-elastic modulus ratio, Young’s modulus, and peak strain—to quantify susceptibility to fracture and plastic strain. With this method, we analyzed the mechanical properties and mineral compositions of 25 downhole core samples from 17 shale gas wells across five formations in the Sichuan Basin. Our results revealed that the proposed method (B3) achieves correlation coefficients of 0.6443 and 0.6438 with conventional elastic strain ratio (B1) and mineral-weighted (B6) methods, respectively. B3 outperforms oversimplified approaches such as quartz content (B5) and Rickman’s modulus–Poisson’s ratio (B4) methods. The method enables cost-effective SBI evaluation using standard triaxial test data without complex stress-unloading experiments. It provides a robust basis for optimizing hydraulic fracturing stage placement—particularly in high-quartz (>70%), low-clay (<15%) intervals (e.g., Longmaxi 11 Formation) where B3 values exceed 80. This work establishes a five-tier classification framework (mechanism/definition/empirical levels) to resolve methodological inconsistencies across 45 existing indices, advancing standardized brittleness evaluation for shale reservoir stimulation.